2009
DOI: 10.1073/pnas.0907967107
|View full text |Cite
|
Sign up to set email alerts
|

Dynein light chain 1 is required for autophagy, protein clearance, and cell death inDrosophila

Abstract: Autophagy is a catabolic pathway that is important for turnover of long-lived proteins and organelles, and has been implicated in cell survival, tumor progression, protection from infection, neurodegeneration, and cell death. Autophagy and caspases are required for type II autophagic cell death of Drosophila larval salivary glands during development, but the mechanisms that regulate these degradation pathways are not understood. We conducted a forward genetic screen for genes that are required for salivary gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…Batlevi et al also reported a decreased number of synaptic boutons in dynein light chain 1 (ddlc1) mutant Drosophila that exhibited attenuated autophagic activity and reduced protein clearance [23] .…”
Section: Autophagy In Synaptogenesismentioning
confidence: 98%
“…Batlevi et al also reported a decreased number of synaptic boutons in dynein light chain 1 (ddlc1) mutant Drosophila that exhibited attenuated autophagic activity and reduced protein clearance [23] .…”
Section: Autophagy In Synaptogenesismentioning
confidence: 98%
“…Polyglutamine diseases demonstrate several characteristic features in patients, such as nuclear inclusions containing the mutant protein, repeat length inversely correlated with age of onset, and age-dependent motor neuron degeneration and impairment. There are several D. melanogaster models of triplet repeat expansion diseases, including fragile X mental retardation with overexpression of the FMR1 gene with various CAG repeat lengths, HD using expression of truncated wild-type and mutant forms of huntingtin/htt , SCA 3 or MachadoJoseph disease expressing truncated ataxin 3 using different glutamine repeat lengths, and SBMA by expressing the human androgen receptor gene with different polyglutamine repeat lengths (Pandey et al, 2007a;Batlevi et al, 2010). All of these models demonstrated that increased poly-Gln expansion led to increased severity of degeneration, age-dependent degeneration, and repeat length-dependent protein aggregation (La Spada and Taylor, 2010).…”
Section: Melanogaster In Drug Discoverymentioning
confidence: 99%
“…Klp98A promotes autophagosome-lysosome fusion, autophagic vesicle acidification and cargo degradation Previous studies have shown that microtubule-and dyneindependent transport of autophagosomes and lysosomes affects not only their intracellular location but also their fusion and activity (Batlevi et al, 2010;Jahreiss et al, 2008;Köchl et al, 2006;Maday et al, 2012), although similar requirements for kinesin-related proteins have not yet been reported. We therefore characterized the functionality of the redistributed autophagic vesicles resulting from Klp98A depletion.…”
Section: Klp98a Depletion Affects Autophagic Vesicle Number and Intramentioning
confidence: 99%